2014
DOI: 10.1021/jm401073p
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 8-Cyclopentyl-2-[4-(4-methyl-piperazin-1-yl)-phenylamino]-7-oxo-7,8-dihydro-pyrido[2,3-d]pyrimidine-6-carbonitrile (7x) as a Potent Inhibitor of Cyclin-Dependent Kinase 4 (CDK4) and AMPK-Related Kinase 5 (ARK5)

Abstract: The success of imatinib, a BCR-ABL inhibitor for the treatment of chronic myelogenous leukemia, has created a great impetus for the development of additional kinase inhibitors as therapeutic agents. However, the complexity of cancer has led to recent interest in polypharmacological approaches for developing multi kinase inhibitors with low toxicity profiles. With this goal in mind, we analyzed more than 150 novel cyano pyridopyrimidine compounds and identified structure activity relationship trends that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…92,107,108 In addition to the above clinical experimental drug compounds, a few pre-clinical CDK4/6 inhibitors, i.e., 7X, AMG925, Compound 6, Compound A and PD0183812, have been reported. [109][110][111][112][113] The chemical structures and CDK inhibitory activity of these compounds are summarized in Table 3. A close examination of the chemical structures of PD0332991, LEE011, LY2835219, AMG925 and Compound A reveals a general N-NH-N sequence of the pyrimidine-amine-pyridine or pyrazineamine-thiazole system.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…92,107,108 In addition to the above clinical experimental drug compounds, a few pre-clinical CDK4/6 inhibitors, i.e., 7X, AMG925, Compound 6, Compound A and PD0183812, have been reported. [109][110][111][112][113] The chemical structures and CDK inhibitory activity of these compounds are summarized in Table 3. A close examination of the chemical structures of PD0332991, LEE011, LY2835219, AMG925 and Compound A reveals a general N-NH-N sequence of the pyrimidine-amine-pyridine or pyrazineamine-thiazole system.…”
Section: Compoundmentioning
confidence: 99%
“…The C6-acetyl group in PD0332991 forms hydrogen bond with the backbone NH of Asp163 of the DFG motif in CDK6. 110 Investigation on the crystal structure of CDK6-Vcyclin in complex with PD0332991 has revealed that selectivity for CDK6 may be achieved by targeting the relatively less conserved hinge region and the pocket near the Phe98 gate keeper in the back of the ATP catalytic site. For instance, this is possible by aromatic sp 2 nitrogen near the rarely conserved His100 (Phe82 in CDK2).…”
Section: Compoundmentioning
confidence: 99%
“…For all samples 0.00154% AcONH -4 was added to water. The aldehydes ( 4a – g ), 11 and the active methylene compounds 10 , 12 13 , 13 16 , 14 and 18 15 were prepared as per the reported procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Mixture of 4-alkylamino-2-methylsulfanyl-pyrimidine-5-carbaldehyde 4 (4.2 mmol), 11 1.2 equiv of active methylene compound and catalytic amount of benzylamine was taken into acetic acid and refluxed for about 6 h. After completion of the reaction (checked with TLC), the reaction mixture was cooled to room temperature, the precipitated product was filtered. The solid was washed with saturated NaHCO 3 , water and dried over vacuum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation